`Fast track` and `traditional path` coaches: affordances, agency and social capital - Rynne, S. (Sport, Education and Society, 2014)
A recent development in large-scale coach accreditation (certification) structures has been the `fast tracking` of former elite athletes. Former elite athletes are often exempted from entry-level qualifications and are generally granted access to fast track courses that are shortened versions of the accreditation courses undertaken by `traditional path` coaches. While formal coach accreditation is not the focus of this research note, it does provide the context for the two coaching case studies. The aim of this article is to consider and contrast the experiences of a former elite athlete and a traditional pathway coach with respect to their development and their trajectory towards employment in high performance coaching settings. The notion of relational interdependence (Billett, 2006) is used to consider the characteristics that particular coaches may bring to their work. In examining the social nature of coaching work and coaching appointments further, it is possible to connect with the notion of social capital (Field, 2006). Informed by accreditation course information (coaching history, aspirations and educational achievements) and three days of in-course observations by the author, the interpretivist case study design incorporated a semi-structured interview with one former elite athlete and one traditional pathway coach during the top level coach accreditation course of one of Australia's most popular team sports. Interviews were transcribed verbatim and coded via a hierarchical content analysis. From this study it was possible to identify a range of affordances that are available to former elite athletes that are not readily accessible for traditional pathway coaches and vice versa. Regarding social capital, former athletes appear to possess greater amounts and are better able to leverage that capital for development and employment. Recommendations are offered and implications discussed for coaches and those individuals and organisations charged with employing high performance coaches.